Postprocessing Study for the Controllable Structures of Ceramic Green Parts Realized by a Flexible Binder Jetting Printing (BJP) Solution - Shu Cao; Fangxia Xie; Xueming He; Chaofeng Zhang; Meiping Wu (Advances in Materials Science and Engineering)
For indirect ceramic additive manufacturing (AM), green parts’ initial densities are low, limiting the postprocessing strengthening under atmospheric pressure. This study employed binder jetting printing (BJP) based on the polycondensation curing of urea-formaldehyde resin to produce series of Al2O3 green specimens with controllable structures. Further, an integrated postprocessing procedure, including the sequential stages of presintering, ceramic slurry infiltration, and final sintering, was conducted on these green specimens with designed structural characteristics for verifying strengthening mechanism. Using a self-developed BJP machine system and the related material which are flexible in process, this study printed green specimens with strong bonding (flexural strength above 6.84 MPa), additionally can regulate their initial densities within the wide range between 21.7%∼43.9%. Infiltrated with ceramic slurry, low-density green specimens were significantly strengthened via final sintering, realizing final densities, flexural strength, and compressive strength of 73.2%, 43.15 MPa, and 331.17 MPa, respectively. In comparison, high-density specimens performing poor infiltration obtained limited density increment after final sintering, but better mechanical properties and surface strengthening were realized, exhibiting final densities, flexural strength, comprehensive strength, surface roughness Ra, and Vickers hardness of 70.1%, 63.22 MPa, 450.18 MPa, 9.73 μm, and 4.58 GPa, respectively. In summary, this study is helpful to provide the technical reference for custom AM ceramic green parts and the postprocessing optimization.